Understanding the mechanisms behind enhanced anaerobic digestion of corn straw by humic acids. (September 2022) - Zhu, Rong; Zhang, Yun; Zou, Hua; Zheng, Yi; Guo, Rong-Bo; Fu, Shan-Fei
Graphical abstract: Highlights: Effects of humic acids on methane yield were related to total solids content. Humic acids had no effect on acidification, but accelerated methane production rate. Humic acids might serve as electron shuttles to promote syntrophic methanogenesis. Abstract: Humic acids (HAs) are abundant on earth, yet their effects on anaerobic digestion (AD) of cellulosic substrate are not fully uncovered. The effects of HAs on AD of corn straw and the mechanisms behind were analyzed in this study. Results showed that the effects of HAs on methane yield were closely related to the total solids (TS) content. At relative high TS content of 5.0%, HAs benefited AD process by increasing 13.8% of methane yield, accelerating methane production rate by 43% and shortening lag phase time by 37.5%. Microbial community analysis indicated that HAs increased the relative abundance of syntrophic bacteria ( Syntrophomonadaceae and Synergistaceae ), facilitating the degradation of volatile fatty acids. HAs might act as electron shuttles to directly transfer electrons to hydrogenotrophic methanogens for CO2 reduction to CH4 . This study provides a simple and efficient strategy to facilitate the AD of cellulosic substrate by HAs addition.